2021
DOI: 10.3904/kjim.2021.326
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine exacerbates tacrolimus-induced renal injury by programmed cell death

Abstract: Background/Aims: Cigarette smoking is an important modifiable risk factor in kidney disease progression. However, the underlying mechanisms for this are lacking. This study aimed to assess whether nicotine (NIC), a major toxic component of cigarette smoking, would exacerbates tacrolimus (TAC)-induced renal injury.Methods: Sprague-Dawley rats were treated daily with NIC, TAC, or both drugs for 4 weeks. The influence of NIC on TAC-caused renal injury was examined via renal function, histopathology, oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…This finding suggests that CTLA4-Ig has a direct effect on protecting TAC-induced renal injury. Our study showed that TAC causes prominent renal damage, which is in accordance with previous studies [20][21][22]. CTLA4-Ig, however, protected against renal injury and oxidative stress from TAC stimulation, indicating that CTLA4-Ig can protect the kidneys from TAC-induced damage in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…This finding suggests that CTLA4-Ig has a direct effect on protecting TAC-induced renal injury. Our study showed that TAC causes prominent renal damage, which is in accordance with previous studies [20][21][22]. CTLA4-Ig, however, protected against renal injury and oxidative stress from TAC stimulation, indicating that CTLA4-Ig can protect the kidneys from TAC-induced damage in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Zhong et al showed that inhibition of ER stress with 4-phenylbutyric acid (4-PBA) mitigates kidney damage and mitochondrial apoptosis due to nephrotoxicity of 3-monochloropropane diol (3-MCPD) [82]. Another study showed that nicotine (NIC), a toxic component of smoke, can accelerate the progression of pre-existing kidney damage by disrupting mitochondrial structural integrity, triggering ER stress, and altering the expression of mitochondrial and ER stress genes [83]. Overall, these findings suggest that the crosstalk between ER and mitochondria has important implications in kidney disorders and that the regulation of both may be a potential therapeutic strategy for kidney protection.…”
Section: Er Crosstalk With Other Organelles In Kidney Diseases Er Cro...mentioning
confidence: 99%
“…Nicotine can increase malignancy through EMT in lung cancer ( Dasgupta et al, 2009 ; Pillai et al, 2015 ; Zhang et al, 2016 ; Du et al, 2018 ). Nicotine can directly induce ER stress response ( Pelissier-Rota et al, 2015 ; Barra et al, 2017 ; Gonzales et al, 2021 ; Jiang et al, 2021 ). In our previous study, we confirmed that nicotine concentration and time dependently increased the expression of ER stress associated apoptosis marker in human bronchial epithelial cells ( Lin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%